PEMBUATAN BISKUIT UBI UNGU (Ipomoea batatas L. Poir) DENGAN SUBTITUSI TEPUNG KACANG TANAH (Arachis hypogaea L.) SEBAGAI ALTERNATIF PEMBERIAN MAKANAN TAMBAHAN (PMT) UNTUK IBU HAMIL - Yeni Tamara; Mulyanita; Yanuarti Petrika (Jurusan Gizi Poltekkes Pontianak, 2025)
Purple sweet potato (Ipomoea batatas L. Poir) is a commonly found sweet potato variety. The purple color of sweet potatoes is caused by the presence of the purple pigment anthocyanin which is spread from the skin to the flesh of the sweet potato. The nutritional content of peanuts includes around 40- 50% fat, around 27% protein, around 18% carbohydrates, and vitamins. To determine the acceptability of panelists covering the color, aroma, taste and texture of Purple Sweet Potato Biscuits (Ipomoea batatas L. Poir) with the Substitution of Peanut Flour (Arachis hypogaea L.) as an Alternative to Supplementary Feeding (PMT) for Pregnant Women. This type of research is experimental research, with hedonic tests on taste, aroma, color and texture. There were 25 panelists. This research was carried out at the Food Technology Laboratory of the Pontiank Ministry of Health Polytechnic. Based on the organoleptic test results, the highest taste was 60% in treatment 3, for aroma the highest was 68% in treatment 3, for color the highest was 52% in treatment 2, and the highest texture was 52% in treatment 2. The acceptability of taste, aroma, color and texture shows that the preferred treatment is treatment 2 with a total score of 402 with a composition of 50% purple sweet potato flour and 20% peanut flour.